Hand hygiene compliance and associated factors among health care workers in a tertiary care hospital: Self reported and direct observation - Rynga, Dabet; Kumar, Shilpee; Gaind, Rajni; Rai, Anil Kumar (International Journal of Infection Control, 2017)
The objective of the present study was to determine the baseline Hand hygiene (HH) compliance rate encompassing all clinical departments of a government sector tertiary care hospital and to determine the factors affecting HH compliance. This was a cross sectional study on knowledge, attitude and practice on HH compliance. Majority of HCWs self reported that they knew about 6 steps of HH (96%) and five moments for HH (89.3%). However only 47.9% knew the right duration of HH by alcohol hand rub and 13.3% had knowledge that all five moments of HH are equally important. Among respondent doctors, the most common reported reason for not practicing HH was non accessibility of sinks or alcohol based hand rub at point of care and amongst nurses it is the belief that their hands are not dirty or HH is not so important in every patient. On being asked why they practice HH, only 8% reported of being motivated by their colleagues. A total of 342 HH opportunities were observed and an overall HH compliance was found to be 14.6%. The necessary infrastructure of the hospital was surveyed for optimal HH practices. It was observed that at many places sinks were not easily accessible and no facility to dry hand after HH. Alcohol based hand rubs were present but not easily accessible. Poster illustrating HH techniques was present only at few places. This study clearly shows that there is a need for the development of strategies to improve HH compliance in HCWs